Performance Evaluation Voice over WLAN Capacity in Three Standards IEEE 802.11 - Sarah Ali Abdullah (Wasit Journal of Engineering Sciences)
In the modern landscape of telecommunication, wireless mobile connectivity and migrating voice telephone services to IP technology are two of the most prominent developments that are transforming the landscape. These two concepts can be utilized together using networks which carry voice services over wireless LAN (VoWLAN). However, due to the unique characteristics of each, certain issues inevitably arise and must be handled to allow for suc-cessful deployment. In this paper OPNET 14.5 Modeler was used to carry out extensive simulation scenarios to examine the single cell WLAN VoIP ca-pacity in regards to three IEEE 802.11 WLAN standards which are (a, b, and g) as well as applying different packet sizes, data rates and codec types for analysis.